VD_FINDINFO Arrêt / 2012 / 81 vom 21. Dezember 2011 - VD Tribunal cantonal (2011)
DEGRÉ DE L'INVALIDITÉ, RENTE D'INVALIDITÉ, ÉVALUATION DE L'INCAPACITÉ DE TRAVAIL, ÉTAT DE SANTÉ | 28 LAI, 4 al. 1 LAI, 16 LPGA, 6 LPGA, 7 LPGA, 8 al. 1 LPGA, 88a RAI